2018
DOI: 10.1111/wvn.12301
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain and Headache in the Active Duty Military Population: An Integrative Review

Abstract: The findings from this review underscore considerable magnitude of MSP in military personnel and expose modifiable risk factors and potential targets for designing nurse-led interventions to improve pain and symptoms in military subpopulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…For instance, military personnel on active duty registered with the US military health insurance program were evaluated in 2012, and 63% were diagnosed with a pain condition ( 21 ). It was found in another study that the rate of drug use for pain increased in proportion to years of active military duty in American soldiers ( 6 ). Because of the high prevalence of pain in AMP, an interdisciplinary medical center was established in U.S. Army for the sole purpose of identifying and treating acute or chronic pain ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, military personnel on active duty registered with the US military health insurance program were evaluated in 2012, and 63% were diagnosed with a pain condition ( 21 ). It was found in another study that the rate of drug use for pain increased in proportion to years of active military duty in American soldiers ( 6 ). Because of the high prevalence of pain in AMP, an interdisciplinary medical center was established in U.S. Army for the sole purpose of identifying and treating acute or chronic pain ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high prevalence of pain in AMP, an interdisciplinary medical center was established in U.S. Army for the sole purpose of identifying and treating acute or chronic pain ( 22 ). Conditions that affect physical and mental health, including sleep disorders, anxiety, depression, substance use disorders, malnutrition, loneliness, fatigue and PTSD, which are common in military personnel, are among the factors that are known to exacerbate pain symptoms and may lead to progression to chronic pain ( 6 , 20 ). Consistent with the literature, we found altered VAS, NDI, NBQ and ODI values in both groups before the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bader et al conducted an integrative review of 26 research articles dating between 2001 and 2016 that examined musculoskeletal pain (MSP) and included active duty military participation (Bader et al, 2018). The purpose of this review was to examine incidence, prevalence, and risk factors for MSP and headaches among the active duty military population.…”
Section: Background and Significancementioning
confidence: 99%
“…The mental and physical demands of deployment readiness training, combat, and other military duties place soldiers at an increased risk of acute and chronic pain (Bader et al, 2018;Reif et al, 2018). In one study, more than 50% of active component (AC) soldiers reported at least one non-combat injury in 2017, 70% of which were physical overuse-related non-combat musculo-skeletal injuries (Molloy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%